Replacement of rapeseed meal by soybean meal protein in broilers ration - Albino, Luiz Fernando T.; Filho, Tércio Michelan; Fialho, Elias Tadeu; Gomes, Paulo Cezar (Pesquisa Agropecuaria Brasileira, 2014)
A randomized block design, with four treatments and four replications was used to study the rapeseed meal as a source of protein in broilers rations at the Centro Nacional de Pesquisa de Suínos e Aves - CNPSA-EMBRAPA - at Concórdia, SC, Brazil, from November/December 1981. The treatments consisted of replacement of 0, 10, 20 and 30% of the soybean meal protein by rapeseed meal. Each replication was formed by 46 broilers (23 males and 23 females), totalizing 736 Pilch broilers. There were no significative differences (P>0.05) among experimental rations for daily weight gain, feed intake and feed conversion. It was concluded that the rapeseed meal can replace up to 30% of soybean meal protein without any damage in performance of the broilers, since the rations were isocaloric and isoproteic.